TINJAUAN YURIDIS PENERAPAN DIVERSI SEBAGAI BENTUK PERLINDUNGAN HUKUMTERHADAPANAK YANG BERKONFLIK DENGAN HUKUM - Semirayasa, I Nyoman; Trisna Dewi, Putu Eka; Dian Laksmi Dewi, Cokorde Istri (Universitas Mahendradatta, 2025)
Children are the next generation of the nation, who will be given responsibility for the development of this nation in the future. However, in today's era, many children's rights are not fulfilled optimally so that children feel they are experiencing injustice in their lives. The emergence of things like this also causes children to fall into free association. From free association that cannot be sorted by children, this association leads to negative things, so that children will easily commit acts of juvenile delinquency. This must be a special concern so that future generations become pioneers in the progress of a country. The importance of protection for children and the fulfillment of children's rights. The approach method used in this legal research is normative juridical. This research is expected to be able to answer the form of legal protection for children in conflict with the law and the obstacles that occur in the process of law enforcement and protection of children.